The putative polyketide cyclase MSMEG_0129 from Mycobacterium smegmatis: purification, crystallization and X-ray crystallographic analysis - Zheng, Shuping (Acta Crystallogr F Struct Biol Commun, 2017)
Mycobacterium tuberculosis Rv0164 has previously been identified as a human T-cell antigen that induces significant production of IFN-γ in human peripheral blood mononuclear cells. M. smegmatis MSMEG_0129 shares 59% sequence identity with Rv0164. Based on sequence alignment, both proteins are predicted to be members of the cyclase/dehydrase family, which is part of a large group of enzymes referred to as type II polyketide synthases (PKSs). In biosynthetic pathways mediated by type II PKSs, cyclases catalyze the conversion of linear poly-β-ketones to cyclized intermediates. To date, no mycobacterial type II PKSs have been reported. Here, the goal is to determine whether these proteins adopt similar folds to reported cyclase structures, and to this end MSMEG_0129 was cloned, expressed, purified and crystallized. An X-ray diffraction data set was collected to 1.95 Å resolution from a crystal belonging to space group P6(2), with unit-cell parameters a = 109.76, b = 109.76, c = 56.5 Å, α = 90, β = 90, γ = 120°. Further crystallographic analysis should establish a basis for investigating the structure and function of this putative mycobacterial type II PKS enzyme.